Analysis of Factors Affecting the Decision of Laborers from Lombok Utara Regency to Become Indonesian Migrant Workers Abroad - Aenun Jariyah; St Maryam; Tuti Handayani; Fassil Eshetu (Socio-Economic and Humanistic Aspects for Township and Industry, 2023)
This study aims to determine the effect of differences in wage levels, marital status and information about destination countries on labor decisions from North Lombok Regency to become Indonesian Migrant Workers. This study uses quantitative methods, data collected by questionnaire and interview techniques. Respondents in this study were 74 people. Data analysis in this study used binary logistic regression. The results of this study indicate that differences in wage levels have a positive effect on labor decisions from North Lombok Regency to become Indonesian migrant workers. The research findings indicate that a person's decision to migrate is influenced by the level of wages in the country that will be the destination of labor.